Pengaruh Model Inkuiri Terbimbing terhadap Motivasi dan Hasil Belajar Siswa pada Pembelajaran IPA Sekolah Dasar - Dian Puspita Sari (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2018)
The purpose of this study is to know the significant differences of motivation and learning outcomes of science students are learned through the implementation of a guided inquiry learning model with a group of students who were taught through conventional learning in class V SDN 02 Cupak Tangah Padang City. Based on the normality and homogeneity test on the data obtained from the experimental group and the control group is normal and homogenous distribution. The hypothesis test is then tested with t-test and shows thitung = 3.027 and ttable = 2,000 with db = 63 (n1 + n2 - 2 = 32 + 31-2 = 63) and 5% significant level. Based on the test tcount> ttable (3.027> 2,000) then H0 rejected and Ha accepted with the conclusion,